Experimental Analysis PVP Coated Silver Nanofluid Properties for Application in Photovoltaic/Thermal (PVT) Collectors - Naderi A.; Gazori H.; Bozegi M. (Journal of Model Based Research, 2020)
Nowadays, supplying energy for the global population has turned into a prominent issue for countries engendering the consumption of huge amounts of fossil fuels which leads to some serious environmental problems. Among the renewable energy technologies, solar collectors can play major role to improve the efficiency, in air conditioning utility systems by minimum pollution. In photovoltaic/thermal (PVT) solar collectors, which are currently considered as the most advanced type to produce electricity and heat simultaneously, working fluid absorbs Energy from photovoltaic (PV) module engendering to decrease temperature of PV module and increase the electricity efficiency and also provide permissible amount of heat for other residential applications. Meanwhile, utilizing nanofluid as the working fluid in collector, regarding that the nanofluid has enhanced thermal properties relative to the base fluid, leads to a higher collector efficiency. In this research, PVP coated silver nanofluid was prepared in three volume concentration being 250, 500 and 1000 ppm by two-step method. To assess the stability of nanofluid the zeta potential is calculated which is obtained -41.6 V. Also, the prominent thermal properties of the nanofluid were analyzed regarding PVT solar collector applications. According to the results, thermal conductivity of the PVP coated silver nanofluid, improves the properties of base fluid, to the extent that thermal conductivity coefficient grows up 50% in some temperatures and increased from 0.594 for base fluid to 1.098 W/mK by escalation of concentration to 1000 ppm. Thus, PVP coated silver nanofluid can be deemed as the vital working fluid to improve the performance of PVT solar collectors.
Keywords: Photovoltaic/thermal (PVT) solar collectors